Ropeginterferon alfa-2b versus phlebotomy in low-risk patients with polycythaemia vera (Low-PV study): a multicentre, randomised phase 2 trial. Issue 3 (March 2021) - Barbui, Tiziano; Vannucchi, Alessandro Maria; De Stefano, Valerio; Masciulli, Arianna; Carobbio, Alessandra; Ferrari, Alberto; Ghirardi, Arianna; Rossi, Elena; Ciceri, Fabio; Bonifacio, Massimiliano; Iurlo, Alessandra; Palandri, Francesca; et al.
Summary: Background: There is no evidence that phlebotomy alone is sufficient to steadily maintain haematocrit on target level in low-risk patients with polycythaemia vera. This study aimed to compare the efficacy and safety of ropeginterferon alfa-2b on top of the standard phlebotomy regimen with phlebotomy alone. Methods: In 2017, we launched the Low-PV study, a multicentre, open-label, two-arm, parallel-group, investigator-initiated, phase 2 randomised trial with a group-sequential adaptive design. The study involved 21 haematological centres across Italy. Participants were recruited in a consecutive order. Participants enrolled in the study were patients, aged 18–60 years, with a diagnosis of polycythaemia vera according to 2008–16 WHO criteria. Eligible patients were randomly allocated (1:1) to receive either phlebotomy and low-dose aspirin (standard group) or ropeginterferon alfa-2b on top of the standard treatment (experimental group). Randomisation sequence was generated using five blocks of variable sizes proportional to elements of Pascal's triangle. Allocation was stratified by age and time from diagnosis. No masking was done. Patients randomly allocated to the standard group were treated with phlebotomy (300 mL for each phlebotomy to maintain the haematocrit values of lower than 45%) and low-dose aspirin (100 mg daily), if not contraindicated. Patients randomly allocated to the experimental group received ropeginterferon alfa-2b subcutaneously every 2 weeks in a fixed dose of 100 μg on top of the phlebotomy-only regimen. The primary endpoint was treatment response, defined as maintenance of the median haematocrit values of 45% or lower without progressive disease during a 12-month period. Analyses were done by intention-to-treat principle. The study was powered assuming a higher percentage of responders in the experimental group (75%) than in the standard group (50%). Here we report results from the second planned interim analysis when 50 patients had been recruited to each group. The trial is ongoing, and registered with ClinicalTrials.gov, NCT03003325 . Findings: Between Feb 2, 2017, and March 13, 2020, 146 patients were screened, and 127 patients were randomly assigned to the standard group (n=63) or the experimental group (n=64). The median follow-up period was 12·1 months (IQR 12·0–12·6). For the second pre-planned interim analysis, a higher response rate in the experimental group was seen (42 [84%] of 50 patients) than in the standard group (30 [60%] of 50 patients; absolute difference 24%, 95% CI 7–41%, p=0·0075). The observed z value (2·6001) crossed the critical bound of efficacy (2·5262), and the stagewise adjusted p value early showed superiority of experimental treatment. Thus, the data safety monitoring board decided to stop patient accrual for overwhelming efficacy and to continue the follow-up, as per protocol, for 2 years. Under the safety profile, no statistically significant difference between groups in frequency of adverse events of grade 3 or higher was observed; the most frequently reported adverse events were neutropenia (four [8%] of 50 patients) in the experimental group and skin symptoms (two [4%] of 50 patients) in the standard group. No grade 4 or 5 adverse events occurred. Interpretation: Supplementing phlebotomy with ropeginterferon alfa-2b seems to be safe and effective in steadily maintaining haematocrit values on target in low-risk patients with polycythaemia vera. Findings from the current study might have implications for changing the current management of low-risk patients with polycythaemia vera. Funding: AOP Orphan Pharmaceuticals, Associazione Italiana per la Ricerca sul Cancro